TANGGUNG JAWAB ETIS PERUSAHAAN DALAM MENJAGA KEBERLAJUTAN PEMBANGUNAN - Nggili, Ricky Arnold (Universitas Kristen Satya Wacana, 2017)
Business ethics bring business back to substantially. The essence to ensure their common prosperity and continuity for life next. Business ethics involves not only the role business people, but also involves the role of government and society. Doing business with ethics placing as human beings, civilized and cultured. Doing business with ethics placed man as beings who are able to work together, sensitivity and concern as well as creatures full responsibilities moral responsibility. The relationship between business, society and government will be harmonious, and able to continue the development of the Indonesian people who are responsible, if the company is conducting its activities in an ethical manner.